Evidence for multi-gap symmetry from grain boundary effects in polycrystalline Ba0.6K0.4Fe2As2 microbridge. (2nd November 2016) - Huang, Ya; Zhou, Xian-Jing; Gao, Zhao-Shun; Wu, Hao; He, Ge; Yuan, Jie; Jin, Kui; Pereira, Paulo J; Ji, Min; An, De-Yue; Li, Jun; Hatano, Takeshi; et al.
Abstract: We studied the grain boundaries within mechanically formed polycrystalline Ba 0.6 K 0.4 Fe2 As2 micro-bridges. By tunneling current across grain boundaries, current–voltage characteristics (IVCs) demonstrated the typical Josephson weak links behavior in micro-bridges. Shapiro steps were observed for the junctions under the microwave radiation at 10 GHz. The temperature dependence of the critical current I c was observed as a shoulder, corresponding to a multi-gap symmetry but not a single-gap s -wave or d -wave.